Soft self-assembly of Weyl materials for light and sound - Fruchart, Michel; Jeon, Seung-Yeol; Hur, Kahyun; Cheianov, Vadim; Wiesner, Ulrich; Vitelli, Vincenzo (NATL ACAD SCIENCES, 2018)
Soft materials can self-assemble into highly structured phases that replicate at the mesoscopic scale the symmetry of atomic crystals. As such, they offer an unparalleled platform to design mesostructured materials for light and sound. Here, we present a bottom-up approach based on self-assembly to engineer 3D photonic and phononic crystals with topologically protected Weyl points. In addition to angular and frequency selectivity of their bulk optical response, Weyl materials are endowed with topological surface states, which allow for the existence of one-way channels, even in the presence of time-reversal invariance. Using a combination of group-theoretical methods and numerical simulations, we identify the general symmetry constraints that a self-assembled structure has to satisfy to host Weyl points and describe how to achieve such constraints using a symmetry-driven pipeline for self-assembled material design and discovery. We illustrate our general approach using block copolymer self-assembly as a model system.
Keywords: BLOCK-COPOLYMERS; PHOTONIC CRYSTALS; ENERGY-BANDS; FERMI ARCS; POINTS; PHASE; LATTICE; SURFACE; STATES; NODES